The surprising temporal specificity of direct-current stimulation - Reinhart, Robert M.G. (Trends Neurosci, 2015)
As studies increasingly use transcranial direct-current stimulation (tDCS) to manipulate brain activity, surprising results are emerging. Specifically, research combining tDCS with electrophysiology is showing that the long-lasting effects of tDCS can counterintuitively influence specific neural mechanisms active for as little as 100 milliseconds during the flow of human information processing.